2012
DOI: 10.1029/2012gb004294
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale lignin particles as sources of dissolved iron to the ocean

Abstract: [1] Primary production in large areas of the open ocean is limited by low iron concentrations. Rivers are potential sources of iron to the ocean, however, riverine iron is prone to intense flocculation and sedimentation in the estuarine mixing zone. Here we report the detection of iron-rich nanoparticles in a typical peatland-draining creek which are resistant against salt-induced flocculation i.e., their behavior is in sharp contrast to the well-known behavior of Fe colloids in river waters. Sample fractionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 96 publications
7
45
1
Order By: Relevance
“…Fluxes of iron from icebergs and sub-glacial melt water streams are likely to be important around Antarctica and glaciated islands in the Southern Ocean (Raiswell et al, 2008;Geibert et al, 2010;Gerringa et al, 2012;Death et al, 2013;Planquette et al, 2013). The outflow of rivers and boreal streams passing through peat land have been shown to be an important source of iron to the Arctic Ocean Krachler et al, 2012;Neubauer et al, 2013;Köhler et al, 2014), and may therefore be important around the Falkland Islands and high latitudes (south of 50°S) of South America (Fig. 4a).…”
Section: Implications For the Shelf Sediment Iron Fluxmentioning
confidence: 96%
“…Fluxes of iron from icebergs and sub-glacial melt water streams are likely to be important around Antarctica and glaciated islands in the Southern Ocean (Raiswell et al, 2008;Geibert et al, 2010;Gerringa et al, 2012;Death et al, 2013;Planquette et al, 2013). The outflow of rivers and boreal streams passing through peat land have been shown to be an important source of iron to the Arctic Ocean Krachler et al, 2012;Neubauer et al, 2013;Köhler et al, 2014), and may therefore be important around the Falkland Islands and high latitudes (south of 50°S) of South America (Fig. 4a).…”
Section: Implications For the Shelf Sediment Iron Fluxmentioning
confidence: 96%
“…The larger the transgression, the larger the volume of reworked and remobilized sediments, which will impact the possible release of iron, coating fine particles; -the flux of river-borne (Severmann et al, 2010) or airborne (e.g., Baddock et al, 2013;Buck et al, 2013) ironcoated particles; -the flux of OM possibly associated with reactive iron (e.g., Barber et al, 2014;Bressac and Huieu, 2013;Krachler et al, 2012;Shigemitsu et al, 2013). Notably, Krachler et al (2012) indicated that peatland-derived iron-bearing lignin particles may have a sufficiently long half-life in ocean water to sustain iron concentration in extended regions of the ocean; -the offshore discharge of anoxic ground waters may generate O 2 -undersaturated bottom water masses that can be advected into nearshore waters (Peterson et al, 2016). These anoxic water masses may thus carry dissolved iron.…”
Section: The Causes Of the Reactive-iron Deficiency Or Presencementioning
confidence: 99%
“…1b). Fulvic acids (Stolpe and Hassellov, 2007) and lignin (Krachler et al, 2012) resist salt-induced flocculation and prevent the aggregation of small Fe(III) colloids due to repulsion effects (Illes and Tombacz, 2006). As a result, organic-Fe(III) complexes with stability constants consistent with those of fulvic acids (Laglera and van den Berg, 2009) are routinely detected in estuaries.…”
Section: Delivery Of Fe To Estuarine Sedimentsmentioning
confidence: 95%
“…Given the poor solubility of Fe(III) at circumneutral pH, it is often assumed that the majority of river-borne dissolved Fe flocculates in coastal areas upon mixing with seawater (Boyle et al, 1977). Several recent studies, however, have demonstrated that Fe(III) may remain in solution in estuarine waters even at high salinities if it is complexed to dissolved http://dx.doi.org/10.1016/j.gca.2014.12.017 0016-7037/Ó 2015 Published by Elsevier Ltd. organic matter (DOM) (Powell and Wilson-Finelli, 2003;Buck et al, 2007;Laglera and van den Berg, 2009;Krachler et al, 2010;Stolpe et al, 2010;Jones et al, 2011;Krachler et al, 2012;Gledhill and Buck, 2012). Simultaneously, relatively high concentrations of dissolved Fe(III) have been identified in coastal sediments (Liang et al, 1993;Luther et al, 1996;Koretsky et al, 2008;Jones et al, 2011), and remobilization and eventual diffusive flux from pore waters has been demonstrated in at least one case (Jones et al, 2011).…”
Section: Introductionmentioning
confidence: 98%